In vivo toxicity study on the effects of aqueous propolis extract from Malaysian stingless bee (Geniotrigona thoracica) in mice - Nurul Alina Muhamad Suhaini; Mohd Faeiz Pauzi; Siti Norazlina Juhari; Khamsah Suryati Mohd; Noor Azlina Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2023)
Geniotrigona thoracica is a stingless bee species of Trigona genus. Propolis resinous is a natural product obtained from a honeybees hive with geographical and floral specifications or exudate as such by-products resulting from a variety of botanical processes. Despite its long use for a variety of health conditions, the toxicity profile of propolis sourced from Malaysian stingless bees has not been sufficiently evaluated. For in vivo toxicity assessment, the acute oral toxicity on the effects of aqueous propolis extracts (APE) was examined. Male mice swiss strain, were subjected to acute toxicity testing for 14 days. The APE at doses of 400, 1000 and 2000 mg/kg body weight was supplemented daily to the mice through oral gavage. The clinical signs of toxicity and general behaviour, body weight, relative organ weight, and histopathology changes were investigated. In vivo study was focused on the acute toxicity testing group consisting of 4 groups including Normal (NS), 400 mg/kg (APE 400), 1000 mg/kg (APE 1000) dan 2000 mg/kg (APE 2000). Regarding the toxicity profile, it is proposed that APE supplementation did not induce any mortality and no visible signs of toxicity. No significant changes in the body and relative organ weight were recorded. All the internal organs of the mice were macroscopically healthy with no gross lesion. Likewise, histopathological examinations of the kidney showed mild to moderate histological lesions. Interestingly, the lesion was adverse with an increased dosage of the extract supplementation. This study proposed APE has considerable anti-inflammatory activities. It also demonstrated that the propolis extract is relatively safe to be consumed orally at a dose of 2000 mg/kg body weight.